Human Sirtuin Regulators: The “Success” Stories - Curry, Alyson M.; White, Dawanna S.; Donu, Dickson; Cen, Yana (Frontiers in Physiology, 2021)
The human sirtuins are a group of NAD+-dependent protein deacylases. They “erase” acyl modifications from lysine residues in various cellular targets including histones, transcription factors, and metabolic enzymes. Through these far-reaching activities, sirtuins regulate a diverse array of biological processes ranging from gene transcription to energy metabolism. Human sirtuins have been intensely pursued by both academia and industry as therapeutic targets for a broad spectrum of diseases such as cancer, neurodegenerative diseases, and metabolic disorders. The last two decades have witnessed a flood of small molecule sirtuin regulators. However, there remain relatively few compounds targeting human sirtuins in clinical development. This reflects the inherent issues concerning the development of isoform-selective and potent molecules with good drug-like properties. In this article, small molecule sirtuin regulators that have advanced into clinical trials will be discussed in details as “successful” examples for future drug development. Special attention is given to the discovery of these compounds, the mechanism of action, pharmacokinetics analysis, formulation, as well as the clinical outcomes observed in the trials.